2005
DOI: 10.1055/s-2005-872435
|View full text |Cite
|
Sign up to set email alerts
|

Transabdominal Measurement of Oxygenation of the Placenta by Near-Infrared Spectroscopy

Abstract: Near-infrared spectroscopy (NIRS) has been used as a noninvasive method for monitoring the real-time oxygenation status in areas such as the brain and striated muscle. Because the oxygenation status of the placenta is closely related to the fetal condition, monitoring placental oxygenation through the maternal abdomen is desirable. We performed transabdominal monitoring of oxygenation of the placenta by NIRS in 11 women. We improved the conventional probe of the NIRO 300 system (Hamamatsu Photonics KK, Hamamat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 1 publication
(1 reference statement)
1
17
0
Order By: Relevance
“…In this regard, noninvasive approaches, such as near-infrared spectroscopy and blood oxygen level-dependent magnetic resonance imaging may prove to be safe and reliable methodologies (15,16). When relative placental ischemia-hypoxia is a component of the disease, then strategies to improve uteroplacental blood flow may be beneficial, to improve placental and fetal growth, and/or alleviate maternal endothelial dysfunction by reducing circulating toxic factors that emanate from the placenta as a consequence of local hypoxia.…”
Section: Discussionmentioning
confidence: 98%
“…In this regard, noninvasive approaches, such as near-infrared spectroscopy and blood oxygen level-dependent magnetic resonance imaging may prove to be safe and reliable methodologies (15,16). When relative placental ischemia-hypoxia is a component of the disease, then strategies to improve uteroplacental blood flow may be beneficial, to improve placental and fetal growth, and/or alleviate maternal endothelial dysfunction by reducing circulating toxic factors that emanate from the placenta as a consequence of local hypoxia.…”
Section: Discussionmentioning
confidence: 98%
“…NIRS has since been utilized in various clinical fields all over the world (Mathieu & Mani 2007;Vardi & Nini 2008). We recently applied NIRS to the human placenta and successfully evaluated concentrations of oxyhemoglobin (HbO2) (Kakogawa et al 2005). Subsequently, we proposed a placental tissue oxygen index (TOI) as an index for the assessment of placental oxygenation (Kawamura et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there are some drawbacks in that the probe can be dislocated as the fetal head descends during delivery. Ramanujam et al 9 and Kakogawa et al 10 found that fetal oxygen dynamics could be measured through the abdominal wall of the mother by NIRS.…”
mentioning
confidence: 99%